Perihemorrhagic ischemia occurs in a volume-dependent manner as assessed by multimodal cerebral monitoring in a porcine model of intracerebral hemorrhage - Orakcioglu, Berk; Kentar, Modar; Schiebel, Patrick; Unterberg, Andreas; Sakowitz, Oliver (Neurocritical care, 2015)
BACKGROUND: Changes in the perihemorrhagic zone (PHZ) of intracerebral hemorrhage (ICH) are variable. Different mechanisms contribute to secondary neuronal injury after ICH. This multimodal monitoring study investigated early changes in the PHZ of ICH. METHODS: Twenty-four swine were anesthetized, ventilated, and underwent monitoring of vital parameters. Next to an intracranial pressure-probe (ICP), microdialysis (MD), thermodiffusion cerebral blood flow (td-CBF), and oxygen probes (PbrO2) were placed into the gray white matter junction for 12 h of monitoring. ICH was induced using the autologous blood injection model. Pre-defined volumes were 0 ml (sham), 1.5 ml ipsilateral (1.5 ml), 3.0 ml ipsilateral (3.0 ml), and 3.0 ml contralateral (3.0 ml contra). RESULTS: ICP equally increased in all groups after ICH. In the 3.0 ml group tissue oxygenation decreased to ischemic values of 9 ± 7 mmHg early after 6 h of monitoring. This decrease was associated with a significant perfusion reduction from 36 ± 8 ml/100 g/min to 20 ± 10 ml/100 g/min. MD correlated with a threefold lactate/pyruvate ratio increase. Measurements in all other groups were unchanged. CONCLUSION: Multimodal monitoring demonstrates volume-dependent changes of tissue oxygenation, blood flow, and ischemic MD markers in the PHZ independent of increased ICP suggesting early moderate ischemia. No evidence was found for the existence of a perihemorrhagic ischemia in the small hematoma groups.